Myanmar Country Forest Note - World Bank (World Bank, Washington, DC, 2020)
Myanmar’s rich tropical forests have historically sustained a sizeable timber industry serving domestic and international markets. Rates of timber extraction rose significantly after 1990, peaking between 2010 and 2015, when controls over forests were weak. Much of the remaining forest estate in government reserves, including areas transferred for community forestry, is now degraded or encroached, and illicit timber harvesting continues, despite a ban on unprocessed log exports and other recent control measures. Ongoing sector reforms and strong government commitments under the Myanmar Restoration and Rehabilitation Program provide a sound basis for moving away from an extractive and inefficient timber industry to a more inclusive and integrated model of forest landscape restoration with greater community ownership and private sector engagement, to ensure that Myanmar’s forests continue to provide sustainable economic, social, and environmental benefits. This requires more diverse management approaches and the collaboration with partners who can expand forest management capacity and coverage, including commercial plantations, community forestry, and engagement with ethnic groups who aspire recognition of rights to forest under customary tenure. It also requires new sources of finance. This Country Forest Note (CFN) summarizes the status of Myanmar’s forests and the investments and policies relevant to the forest sector. It aims to inform a strategic, programmatic approach for the management of forests, built on an understanding of the cross-sectoral challenges that the sector faces. It builds on the Forest Sector Report of the Country Environmental Analysis by filing gaps in data and knowledge, including from new studies on private sector plantations, woodfuel, and forest tenure. The CFN takes a uniquely cross-sectoral perspective that considers how other sectors impact forests, and vice versa, and where opportunities lie for better cross-sectoral coordination.